Performance and digestive organ profile of Wandering Whistling Duck fed different protein levels - Jamilah, J.; Mahfudz, L. D.; Suprijatna, E.; Wahyuni, H. I.; Sugiharto, S. (Diponegoro University, 2025)
This study investigated the effects of different dietary protein levels on the performance and diges-tive tract profile of Wandering Whistling Ducks. A total of 108 5-month-old Wandering Whistling Ducks were reared intensively for three months (one-month rearing and feed adaptation period fol-lowed by two months of dietary intervention). The dietary treatments comprised of three protein levels: T1 12%, T2 15%, and T3 18%. Each treatment consisted of nine replications, with each experimental unit consisted of four Wandering Whistling Ducks. The parameters measured in this study were feed consumption, water consumption, feed-to-water ratio, body weight gain, relative weight and length of digestive organ, villus height, crypt depth, villus-to-crypt ratio, histopathological features, digestive tract pH, and ileal bacteria counts. The data were analyzed using analysis of variance followed by Dun-can’s multiple range test. The results indicated that dietary protein levels significantly affected feed consumption, body weight gain, ileal crypt depth, cecal lactic acid bacteria, and gizzard pH. Other pa-rameters showed no significant response to different protein levels. Based on these findings, it was concluded that a dietary protein level of 18% yielded the most favourable outcomes in terms of growth performance and the digestive tract profile of Wandering Whistling Ducks.